Innovation on the Island: Sri Lankan Solutions for a Plastic-free Future - Jayathunga, J.N.D. (Central Environmental Authority, Sri Lanka, 2025)
Sri Lanka, the teardrop-shaped island in the Indian Ocean, is making waves in the global fight against plastic pollution. Once known for its pristine beaches and rich biodiversity, the country now stands at the forefront of innovative, sustainable solutions that blend science, tradition, and community action. This article, “Voices for a Plastic-Free Planet 2025,” explores how Sri Lankan researchers, entrepreneurs, and citizens are transforming a national challenge into a story of hope and creativity. From converting coconut husks into biodegradable packaging and crafting edible seaweed wrappers to producing fuel from discarded plastics, local innovators are redefining what it means to live sustainably. Grassroots movements, too, are taking charge—villages and urban neighborhoods are creating “plastic-free zones” and reviving eco-friendly customs such as using banana leaves, clay pots, and cloth bags. Supported by progressive government policies like bans on single-use plastics and grants for green startups, these efforts reveal the power of collective action. Yet, challenges remain—higher production costs, limited infrastructure, and the need for wider awareness. Despite these hurdles, Sri Lanka’s journey illustrates that even small nations can lead transformative environmental change. By weaving innovation with heritage and policy with participation, the island demonstrates a clear message to the world: a plastic-free future is possible when creativity, collaboration, and commitment come together.
Keywords: Plastic; Plastic free-future